2019
DOI: 10.1111/1365-2656.13155
|View full text |Cite
|
Sign up to set email alerts
|

Fitness consequences of different migratory strategies in partially migratory populations: A multi‐taxa meta‐analysis

Abstract: Partial migration—wherein migratory and non‐migratory individuals exist within the same population—represents a behavioural dimorphism; for it to persist over time, both strategies should yield equal individual fitness. This balance may be maintained through trade‐offs where migrants gain survival benefits by avoiding unfavourable conditions, while residents gain breeding benefits from early access to resources. There has been little overarching quantitative analysis of the evidence for this fitness balance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 96 publications
5
60
4
Order By: Relevance
“…Interestingly, this evolutionary inertia due to this pattern of phenotypic expression has hitherto not been considered in phenotypic evolutionary models of partial migration [18]. These models generally assume that for partial migration to persist the fitness of migrants and residents should be approximately equal over time, which is at odds with empirical findings [32]. Our model demonstrates that even in the presence of large fitness differences, partially migratory populations may evolve rapidly and persist during a long period of time, as a consequence of the evolutionary dynamics of semi-continuous threshold traits.…”
Section: Discussioncontrasting
(Expert classified)
See 1 more Smart Citation
“…Interestingly, this evolutionary inertia due to this pattern of phenotypic expression has hitherto not been considered in phenotypic evolutionary models of partial migration [18]. These models generally assume that for partial migration to persist the fitness of migrants and residents should be approximately equal over time, which is at odds with empirical findings [32]. Our model demonstrates that even in the presence of large fitness differences, partially migratory populations may evolve rapidly and persist during a long period of time, as a consequence of the evolutionary dynamics of semi-continuous threshold traits.…”
Section: Discussioncontrasting
(Expert classified)
“…The best territories, however, are occupied by residents, which have the advantage of prior residency [28,29]. Furthermore, a number of studies have shown that residents have higher fitness than (short-distance) migrants [30][31][32], and that birds with longer migration distance have lower fitness [33,34]. Based on these findings, we designed three continuous fitness functions: one where the decline in fitness with increasing migratory activity is exponential, one where it is linear and one that follows a logistic relationship (figure 1).…”
Section: (Ii) Tested Parametersmentioning
confidence: 99%
“…Surprisingly few previous studies have tested for differential survival of migrants versus residents, or hence quantified survival selection, under any conditions and in any taxa (Buchan et al., 2019; Reid et al., 2018). Recent studies demonstrated higher survival in migrants than residents in blackbirds Turdus merula (Zúñiga et al., 2017) and roach Rutilus rutilus (Skov et al., 2013), but this was not evident in American dippers Cinclus mexicanus (Green et al., 2015), and residents had higher survival than migrants in elk Cervus canadensis (Hebblewhite & Merrill, 2011) and red‐spotted newts Notophtalmus viridescens (Grayson et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Partial migration, where migrant and non-migrant individuals exist within the same population 14 , 15 , provides a powerful natural experiment to explore these carryover effects, by comparing fitness parameters of migrants and residents 16 . Although parity in fitness under both strategies is necessary for the evolutionary maintenance of partial migration 14 (especially if migratory strategy is heritable 17 ), it is hypothesised that this balance is maintained through trade-offs where migratory costs that reduce fitness in one parameter (survival or breeding success) are compensated by higher fitness in another 14 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of within-population partial migration in birds are in short-distance systems 16 . Here we examine carryover effects in an unusual example of long-distance partial migration (lesser kestrels, Falco naumanni ), where non-migratory individuals are fully resident in the Spanish breeding grounds throughout the year, while migrants undertake a c. 3000-km trans-Saharan migration, such that individuals may be exposed to very different costs between the two strategies.…”
Section: Introductionmentioning
confidence: 99%